Leibniz's justification for the principle of sufficient reason (mainly) in the correspondence with Clarke - Lodge, P (Mentis Verlag, 2019)
The aim of this paper is to shed light on Leibniz’s justification of the Principle of Sufficient Reason. It approaches this issue through a close textual analysis of the correspondence with Samuel Clarke and a more abstruse and lesser-known writing, ‘Leibniz’s Philosophical Dream’.